Thermodynamic modeling of calcium sulfate hemihydrate formed from seawater and concentrated brine at elevated temperature - Ali Al-Hamzah; Caillan J. Fellows; Christopher M. Fellows (Case Studies in Chemical and Environmental Engineering)
Formation of hard scale, predominantly calcium sulfate, is the limiting factor in the operation of multi-stage flash (MSF) thermal desalination of seawater, restricting the top temperature and top brine concentration that can be achieved. More accurate prediction of the solubility product of calcium sulfate hemihydrate, the scaling species formed initially above 100 °C, under conditions found in MSF plants, would allow better control of MSF operations. In this report literature data for calcium sulfate solubility is analysed and the Pitzer model applied to determine solubility product values at temperatures up to 148 °C and total dissolved solids concentration up to 99 g/L (equivalent to a concentration factor for Arabian Gulf seawater of 2.2). From these an analytical expression is determined for predicting the supersaturation index (SI) under these conditions to simplify the task of MSF plant operators, SI = 61.5891–0.4783 ln(TDS) + 0.3223 (ln(TDS))2–31.7890 ln(T) + 3.7977 (ln(T))2